Studies on Monitoring and Tracking Genetic Resources: An Executive Summary. Issue 1 (July 2009) - Garrity, George; Thompson, Lorraine; Ussery, David; Paskin, Norman; Baker, Dwight; Desmeth, Philippe; Schindel, D.; Ong, P.
Abstract The principles underlying fair and equitable sharing of benefits derived from the utilization of genetic resources are set out in Article 15 of the UN Convention on Biological Diversity, which stipulate that access to genetic resources is subject to the prior informed consent of the country where such resources are located and to mutually agreed terms regarding the sharing of benefits that could be derived from such access. One issue of particular concern for provider countries is how to monitor and track genetic resources once they have left the provider country and enter into use in a variety of forms. This report was commissioned to provide a detailed review of advances in DNA sequencing technologies, as those methods apply to identification of genetic resources, and the use of globally unique persistent identifiers for persistently linking to data and other forms of digital documentation that is linked to individual genetic resources. While the report was written for an audience with a mixture of technical, legal, and policy backgrounds it is relevant to the genomics community as it is an example of downstream application of genomics information.